Economic perspective for PV under new Italian regulatory framework. (May 2017) - Lazzeroni, P.; Olivero, S.; Repetto, M.
Abstract: A PV market decrease in Italy has been observed in the last years due to the closure of the feed-in-tariff contribution from the Italian Government. However, a new opportunity introduced by the Italian Authority for Energy (AEEGSI) could represent a possible driver for the Italian PV market. A resolution of the AEEGSI has introduced in 2013 the technical and economic rules for a new way of exchanging power between two companies: one energy producer based on Renewable Energy Sources (RES) and a final End-User. This new opportunity paves the way for new PV investments and an increase in RES consumption, since energy can be traded free from the network charges. A mutual advantage is in fact present for both RES producers and End-Users: RES producers sell their energy locally at a price higher than that the zonal-market one, while End-User energy bill is reduced. The present study defines a method for finding the best match between Producer and End-User advantages by stating the rules for the definition of the optimum sizing of a PV plant supplying a local industrial company. Net-metering contribution is also considered as a further economic boost for investment in the PV market. A further element of the analysis is devoted to the tradeoff of energy price between the two companies. Starting from the current Italian market energy prices, the study highlights how the economic indicators of the PV investor are influenced by the final price of energy paid by the End-User. The perspectives for PV investors is positive even without an economic incentive scheme of RES production.